PENGARUH PROFITABILITAS, KEBIJAKAN DIVIDEN, KEBIJAKAN UTANG, DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2018 - 2020) - Dhena Alinda Milenia; Dul Muid (Diponegoro Journal of Accounting, 2022)
This study aims to examine the effect of profitability, dividend policy, debt policy, and investment decisions on the value of manufacturing companies listed on the Indonesia Stock Exchange for the period 2018 until 2020. This study refers to previous research conducted by Putri and Rachmawati (2018).Company ratios such as profitability (ROE), dividend policy (DPR), debt policy (DER), and investment decisions (TAG) are considered to have an influence on firm value (PBV). In this study using multiple linear regression analysis method with the help of SPSS, some classical assumption test to meet the regression test, and other tests namely hypothesis testing (fit and goodness).This study found that firm value can be influenced by profitability, dividend policy, debt policy, and investment decisions and is able to explain the relationship between the dependent and independent variables. The results show that profitability, dividend policy, and debt policy have a positive and significant effect on the value of manufacturing companies. Meanwhile, investment decisions have no significant effect on the value of manufacturing companies in Indonesia.